High‐level expression and characterization of a new κ‐carrageenase from marine bacterium Pedobacter hainanensis NJ‐02. (9th March 2018) - Zhu, B.‐W.; Xiong, Q.; Ni, F.; Sun, Y.; Yao, Z.
Abstract: A novel κ ‐carrageenase gene ( CgkB ) has been cloned from Pedobacter hainanensis NJ‐02 and expressed heterologously in Escherichia coli BL21 (DE3). It consisted of 1935 bp and encoded 644 amino acid residues with a molecular weight of 71·61 kDa. The recombinant enzyme showed maximal activity of 2458 U mg −1 at 40°C and pH 8·0. Additionally, it could retain more than 70% of its maximal activity after being incubated at pH of 5·5–10·0 below 40°C. K + and a broad range of NaCl can activate the enzyme. The K m and V max of CgkB was 2·4 mg ml −1 and 126 mmol mg −1  min −1 . The ESI‐MS analysis of hydrolysates indicated that the enzyme can endolytically depolymerize the carrageenan into tetrasaccharides and hexasaccharides. The results indicated that the enzyme with high activity could be a valuable enzyme tool to produce carrageenan oligosaccharides with various activities. Significance and Impact of the Study: Enzymatic preparation of carrageenan oligosaccharides has drawn increased attention due to their various physiological activities. It is urgent to explore enzyme tools with higher activity and better stability. In this work, a novel κ ‐carrageenase was identified and characterized from marine bacterium Pedobacter hainanensis NJ‐02. The enzyme with high activity could be a valuable tool to produce carrageenan oligosaccharides with various activities Abstract : Significance and Impact of the Study: Enzymatic preparation of carrageenan oligosaccharides has drawn increased attention due to their various physiological activities. It is urgent to explore enzyme tools with higher activity and better stability. In this work, a novel κ ‐carrageenase was identified and characterized from marine bacterium Pedobacter hainanensis NJ‐02. The enzyme with high activity could be a valuable tool to produce carrageenan oligosaccharides with various activities.